Development of 1-inch boiler tube inspection robot - Shah M.A.A.; Sahari K.S.M.; Jalal M.F.A.; Anuar A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Boilers; Industrial electronics; Locks (fasteners); Machine design; Magnetism; Robots; Tubes (components); Wheels; Design and Development; Future improvements; Inspection robots; Magnetic wheels; modular; Robotic technologies; Utility companies; Visual inspection; Inspection